Addressing health and social care during and beyond COVID-19: the importance of implementation science - Helen Skouteris (Sax Institute, 2021)
Implementation science is increasingly relevant and important as we move beyond the immediate response to, and curtailing of, the coronavirus disease 2019 (COVID-19) pandemic. Understanding how to prevent the spread of the virus, and treating and improving the lives of those infected, requires translating knowledge into action, and implementing evidence-based interventions. We know the direct impacts of COVID-19, and associated interventions to address it, will not be felt equally across all population groups. Hence, it is proposed that the integration of health and social sciences is fundamental to mitigate potential adverse impacts of interventions for COVID-19. In this paper I argue that the involvement of consumers and the community in the quest to combat and recover from the COVID-19 pandemic will enable social equity, as demonstrated by a case study.